Hsian-Tsao (Mesona chinensis Benth.) Extract Improves the Thermal Tolerance of Drosophila melanogaster - Huang, Yan; Cai, Pumo; Su, Xinxin; Zheng, Mingjing; Chi, Wenwen; Lin, Shaoling; Huang, Zhiwei; Qin, Si; Zeng, Shaoxiao (Frontiers in Nutrition, 2022)
Global warming has prompted scientific communities to consider how to alleviate thermal stress in humans and animals. The present study assessed the supplementation of hsian-tsao extract (HTE) on thermal stress in Drosophila melanogaster and preliminarily explicated its possible physiological and molecular mechanisms. Our results indicated that the lethal time for 50% of female flies fed on HTE was significantly longer than that of male flies at the same heat stress temperature. Under thermal stress, the survival time of females was remarkably increased in the HTE addition groups compared to the non-addition group. Thermal hardening by acute exposure to 36°C for 30 min (9:00 to 9:30 a.m.) every day could significantly prolong the longevity of females. Without thermal hardening, HTE increased the antioxidant capacity of females under heat stress, accompanied by an increment of catalase (CAT) activity, and the inhibition for hydroxyl radicals (OH⋅) and superoxide anions (⋅O2–). Superoxide dismutase (SOD) activity and the inhibition for ⋅O2– was significantly affected by thermal hardening in the non-HTE addition groups, and significant differences were shown in CAT and SOD activities, and the inhibition for ⋅O2– among groups with thermal hardening. After heat exposure, heat shock protein 70 (Hsp70) was only up-regulated in the group with high levels of added HTE compared with the group without and this was similar in the thermal hardening group. It was concluded that the heat stress-relieving ability of HTE might be partly due to the enhancement of enzymatic activities of SOD and CAT, and the inhibition for OH⋅ and ⋅O2–. However, the expression levels of Hsp70 were not well related to thermal tolerance or heat survival.